Attractiveness of public spaces in small and medium- sized cities - a condition for their development - Kobylarczyk, Justyna; Kuśnierz-Krupa, Dominika; Paprzyca, Krystyna (КНУБА, 2018)
The irrational spatial economy is observed in many small or medium-sized towns and cities. It can acquire the form of empty, undeveloped areas, degraded buildings as well as scattered building development on the outskirts of the cities.
Привабливість громадських просторів в малих і середніх містах як умова їх розвитку
Atrakcyjność przestrzeni publicznych w miastach małych i średniej wielkości – warunkiem ich rozwoju
Keywords: attractiveness; competitiveness; functional and spatial clusters in public spaces; привабливість; конкурентність; функціонально-просторові кластери в громадських просторах; atrakcyjność; konkurencyjność; klastry funkcjonalno- przestrzenne w przestrzeniach publicznych; 711.4